Pore structure characterization of coal by NMR cryoporometry. (15th February 2017) - Zhao, Yixin; Sun, Yingfeng; Liu, Shimin; Wang, Kai; Jiang, Yaodong
Highlights: NMR cryoporometry was adopted to the characterization pore size distribution in coal. NMR intensity result for the coal was calibrated to get reliable pore size distribution. NMR cryoporometry yields a higher pore volume magnitude, compared to low-temperature liquid nitrogen adsorption and desorption (LTNAD). Pore size distribution can be directly obtained by NMR cryoporometry, based on the linear relation between pore volume and signal intensity and the relationship between the melting point and pore size. Abstract: The characterization of coal pore structure is extremely important to coalbed methane exploitation and the prevention of gas disaster in coal mines. Various techniques have been employed to characterize the pore size distribution (PSD) in coals. Nuclear magnetic resonance (NMR) cryoporometry is a relative new technique that can be applied to obtain PSD of porous materials. However, seldom works has been done on coals by NMR cryoporometry. In this paper, PSD of six coal samples ranges from medium to high rank are measured by NMR cryoporometry. Low-temperature liquid N2 adsorption and desorption (LTNAD) experiments are also carried out on the same samples for the comparison analysis. NMR cryoporometry can directly obtain the PSD from the linear relation between pore volume and signal intensity and the relationship between the melting point and pore size. It was also found that there is a good correlation between the results obtained by NMR cryoporometry and LTNAD. It was found that NMR cryoporometry yields higher pore volume value than LTNAD. Drying induced pores shrinkage/collapse in LTNAD measurement is the main reason causing pore volume measured by NMR cryoporometry is larger than by LTNAD. We also found the difference between NMR and LTNAD correlated with the coal moisture content. Based on the obtained experimental data, it is found that the influence of moisture content on the difference between these two techniques decreases with the increase of pore specific volume.